EXPLORING MECHANICAL INJURIES: THEIR EFFECTS ON SKIN AND FASCIA IN ENDURANCE SPORTS – A SYSTEMATIC REVIEW - Barbara Kujawa,; Dominika Kozłowska,; Klaudia Jasik-Zawadka,; Paweł Jankowski,; Antoni Dondajewski,; Kamil Rajczyk, (International Journal of Innovative Technologies in Social Science, 2025)
Chronic mechanical injuries in endurance athletes often cause significant changes in the skin and fascia, which in turn impacts the overall functioning of the musculoskeletal system. These changes can lead to limited mobility, impaired biomechanics, and an increased risk of further injury. Effectively preventing and managing these issues requires an interdisciplinary approach that combines fascial therapy with stress reduction techniques. This comprehensive model not only protects athletes but also supports their optimal recovery and performance.Aim of the study: This study aims to synthesize current knowledge on the impact of repetitive mechanical micro-injuries on the skin and fascial structures in endurance athletes. The review explores the underlying injury mechanisms, fascial responses to sustained mechanical stress, dermatological manifestations resulting from chronic load, as well as preventive and therapeutic approaches relevant to this population.Materials and Methods: A comprehensive literature search was conducted across the PubMed, Google Scholar, Medline, and Scopus databases. Search terms included: “mechanical injuries”, “endurance sports”, “micro-injuries and skin”, and “micro-injuries and fascia”.Results and Conclusions: Recurrent mechanical strain in endurance sports disciplines—such as running, cycling, and triathlon—has been found to impact both superficial (cutaneous) and deep (fascial) tissue structures. The skin can act as a visible marker of biomechanical overload, potentially guiding clinicians toward the need for further diagnostic evaluation. Effective prevention and treatment strategies require a collaborative, interdisciplinary approach involving dermatology, orthopedics, and physiotherapy.